Farmers Perception towards the extent of Land Degradation in the case of Essera Woreda, Dawuro Zone Southwest Ethiopia - Adare, Barena (International Journal of Scientific Research in Civil Engineering, 2021)
The aim of this study to assess farmer’s perception towards the extent of land degradation in oki Keble. Specifically the study intended to analyze farmers’ knowledge of land degradation and perceived impacts, to identify the traditional knowledge, techniques and practices used by households to control land degradation, to explore farmers’ knowledge of the existing soil and water conservation measures and constraints to their adoption. The various data collection tools used for the collection of qualitative and quantitative information and this qualitative and quantitative information were analyzed by descriptive statistics such as percentage and table. The results of house hold survey indicate that farmers were aware of the on-going soil degradation and of several erosion control measure and land husbandry practices. They perceive soil degradation mainly, decreasing fertility, changing in appearance and becoming stony. The most frequently mentioned soil erosion indicators were rill and gully formation followed by exposed underground rocks, soil becoming coarse and stony, and topsoil removal. The most important perceived indicator of soil fertility loss was reduced crop yield, followed by poor crop performance and yellowing of the crop. Majority of farmers preferred soil bund, crop rotation and counter ploughing for soil and water conservation and chemical fertilizer, crop rotation and mixed cropping for soil fertility amendment while they did not recognize agro-forestry and farm yard manure as a conservation and fertility amendment measure. Farmers faced several constraints in adopting soil and water conservation measures: decrease in farm size, its inconvenience during for free movement of oxen plough, and multiplication of mistakes in the construction soil bunds.
Keywords: Land Degradation; Conservation; Perception; Soil Erosion